Implementasi Blended Learning Berbasis Problem Solving Chat Untuk Meningkatkan Keterampilan Pemecahan Masalah - Anita Anggraini; Johan Syahbrudin (Faculty of training and education, Pamulang university, 2021)
ABSTRACTThis research aims to determine the effectiveness of using blended learning based on problem solving chat through Learning Management System of Pamulang University in improving problem solving skills. This study was included in the pre-experiment research using One-group pretest-posttest design. The research data were analyzed using a paired t-test with sample requirements normally distributed. It was followed by the effect size and power test to find out how much the effect was. The results of this research indicate that the use of blended learning based on problem solving chat has an effect on improving problem solving skills. The d value is obtained of 0.28 which is included in the moderate category, which means that the use of blended learning based on problem solving chat has an influence in improving the problem solving skills of students with moderate categories. So that the results of this research are expected to be a reference for educators to be able to apply blended learning based on problem solving chat when the learning objective is to improve students' problem solving skills.Keywords: blended learning; problem solving chat; problem solving skillsABSTRAKRiset ini bertujuan untuk mengetahui keefektifan penggunaan blended learning berbasis problem solving chat melalui Learning Management System Universitas Pamulang dalam meningkatkan keterampilan pemecahan masalah. Riset ini merupakan penelitian pra eksperimen menggunakan one-group pretest-posttest design. Data hasil riset dianalisis menggunakan paired t-test, kemudian dilanjutkan dengan uji effect size and power untuk mengetahui seberapa besar efektifitas pengaruh tersebut. Hasil riset ini menunjukkan bahwa penggunaan blended learning berbasis problem solving chat berpengaruh terhadap peningkatan keterampilan pemecahan masalah. uji effect size and power diperoleh nilai d sebesar 0,28 termasuk dalam kategori sedang. Hasil riset ini diharapkan dapat menjadi salah satu referensi bagi pendidik untuk dapat menerapkan pembelajaran blended learning berbasis problem solving chat ketika tujuan pembelajarannya untuk meningkatkan keterampilan pemecahan masalah peserta didik.Kata kunci: blended learning; problem solving chat; keterampilan pemecahan masalah